2014
DOI: 10.1177/0255761413515819
|View full text |Cite
|
Sign up to set email alerts
|

Becoming music teacher educators: Learning from and with each other in a professional development community

Abstract: During this heuristic phenomenological inquiry, we examined our lived experiences as five women (three doctoral students, two early career faculty) in the process of becoming music teacher educators participating in a year-long, online, group-facilitated professional development community (PDC). Data included recorded meetings via Skype, journal entries via a private Facebook blog, and written introductory and final reflection statements. The three core themes that emerged from the data were as follows: (a) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 18 publications
2
41
1
Order By: Relevance
“…Preparation to conduct research is clearly one of the goals and components of a PhD degree. Several authors have lamented, however, that many recipients of the doctorate in music education do not publish a study based on their dissertation, do not continue to conduct and publish research after graduation, and are not prepared adequately or feel unprepared to do so (Humphreys, 2006; Pellegrino, Sweet, Kastner, Russell, & Reese, 2014; Sims, 2016; Sims & Cassidy, 2015). Although Martin (2016) found that the means for the music education doctoral student participants in her study placed them within her “very confident” category as K–12 teacher educators, their mean responses were only within her “confident” category in their abilities to contribute original research or train and mentor graduate students.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation to conduct research is clearly one of the goals and components of a PhD degree. Several authors have lamented, however, that many recipients of the doctorate in music education do not publish a study based on their dissertation, do not continue to conduct and publish research after graduation, and are not prepared adequately or feel unprepared to do so (Humphreys, 2006; Pellegrino, Sweet, Kastner, Russell, & Reese, 2014; Sims, 2016; Sims & Cassidy, 2015). Although Martin (2016) found that the means for the music education doctoral student participants in her study placed them within her “very confident” category as K–12 teacher educators, their mean responses were only within her “confident” category in their abilities to contribute original research or train and mentor graduate students.…”
mentioning
confidence: 99%
“…Given the complexity of the job of music teacher educator, the transition from doctoral student to music education faculty member is likely to present a variety of challenges and may even be considered a struggle for some (Martin, 2016). A growing body of literature in music education has begun to address related issues, including the development of identity (Bond & Koops, 2014; Conway, Eros, Pellegrino, & West, 2010), socialization into teaching (Conkling & Henry, 2008), learning to teach graduate students (Conway et al, 2016), peer mentoring (Draves & Koops, 2011), and the role of a professional development community (Pellegrino et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, results from this study may reflect selection bias. Though researchers have suggested music education doctoral students may struggle to adopt the identity of "music teacher educator" (Bond & Koops, 2014;Conway et al, 2010;Pellegrino et al, 2014), results from this study showed that music education doctoral students identified more strongly with the identities of "music teacher educator" and "teacher mentor" than identities such as "student" or "K-12 music teacher." This association could be attributed to the fact that the majority of participants were relatively far into their programs, averaging around 44 hours completed toward the doctoral degree.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 55%
“…Goddard, et al, 2007;Bryk et al, 1999;Caron & M. J. McLaughlin, 2002;Hollins, 2004;McDuffie, 2009;Pounder, 1999;Ronfeldt et al, 2015;Rosenholtz, 1989;Shachar & Shmuelevitz, 1997;Sun, 2016). Concerning music teachers, a number of qualitative studies have documented the importance of collaboration (Battersby & Verdi, 2015;Gruenhagen, 2012;Kastner, 2014;Pellegrino, Sweet, Derges-Kastner, Russell, & Reese, 2014;Sindberg, 2011;Sindberg, 2016;Stanley, 2012;Stanley, Snell, & Edgar, 2014). I found no quantitative studies on collaboration amongst music teachers, prompting the current pilot study on K-12 music teachers in Iowa.…”
Section: Chapter 1 Introductionmentioning
confidence: 91%